Patient scheduling in hemodialysis unit using simple heuristic - Sundar, Ashweena; Ab Rahmin, Nor Aliza; Chen, Chuei Yee; Mohamed Ali, Nazihah (Malaysian Mathematical Science Society (PERSAMA), 2021)
This paper study a patient scheduling and nurse assignment problem in the hemodialysis unit. A long waiting time can cause dissatisfaction among patients, and it might affect their health condition. We aim to minimize the waiting time before and after the dialysis treatment by considering patients’ satisfaction. As the model consumes a high computational time to solve for a large-scale instance, we developed a simple heuristic to deal with the problem. The results show that solutions obtained by the simple heuristic are of good quality and has significantly reduced the computational time even when considering more patients on the waiting list.